Capacity Building in Local Government - TRIANA, ROCHYATI (Universitas Muhammadiyah Yogyakarta, 2013)
The aim of this research is to examine the concept of local government capacity building in boththeoretical and operational aspects, regarding especially with local authorities in Indonesia, after theenforcement of regional autonomy. This is a basic research (fundamental research) of library researchtype. Data collection technique involves using data sourced from a variety of secondary sources, as itshould be; books, journals, and related legislation. To draw a conclusion regarding with the building ofregional capacity after the implementation of regional autonomy, the data are analyzed using descriptiveanalysis technique; that is, examining secondary data based on Indonesian condition. This researchconcludes that Capacity Building is a huge job for the an autonomous local government, particularlywhen dealing with the system which is deemed to prioritize self-serving rather than public serving; yetthis capacity building mission deserves to fight for. Stakeholders (other than legislatives) need toregularly monitor the improved performance of the government so that the high expectation of the societycould be fulfilled through the enforcement of regional autonomy.